Effect of Various Mulching Materials on Yield and Quality of Okra (Abelmoschus Esculentus) in Mahottari, Nepal - Chaulagain, Supriya; Shrestha, Sailesh; Paudel, Subodh; Rajbahak, Deena; Chaudhary, Bijay; Shrestha, Susma; Adhikari, Shreeram; Rajput, Avishek Singh (International Journal of Applied Sciences and Biotechnology, 2024)
An experiment was conducted from April to July 2023 in the Mahottari district of Nepal to evaluate the influence of various mulching materials on the yield and quality of okra, specifically the Arka Anamika variety. The study employed a Randomized Complete Block Design (RCBD) with four replications and included five treatment variations: T1 (Control), T2 (Black plastic), T3 (Silver plastic), T4 (Rice straw), and T5 (Sawdust). The findings revealed that the type of mulch significantly affected all growth and yield parameters. Among all treatments, black plastic mulch yielded the highest seed germination rate at 89.01%, while the control plot had the lowest rate at 68.00%. At 35, 50, and 65 days after sowing (DAS), plants in black and silver plastic mulch plots were significantly taller than those in other treatments. Black plastic mulch also enhanced leaf number, promoted earlier flowering, and produced higher yields compared to bare soil, with silver plastic mulch being the next most effective. Crops grown with plastic mulch exhibited superior vegetative growth and yield attributes compared to those with organic mulches. The highest productivity was recorded in the black plastic mulch treatment (30.00 Mt/ha), followed by silver plastic mulch (27.00 Mt/ha). Moreover, black plastic mulch resulted in the highest net return and benefit-cost ratio (3.23), while the control plot had the lowest (1.8). Consequently, the use of plastic mulch, particularly black plastic mulch, is recommended to enhance vegetable production in the research area.Int. J. Appl. Sci. Biotechnol. Vol 12(4): 207-114.